2018
DOI: 10.3928/23258160-20180814-02
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal Retinal Vessel Density Assessment by Optical Coherence Tomography Angiography in Healthy Eyes

Abstract: receives research support from Carl Zeiss Meditec, Topcon, and OptoVue. Nadia K. Waheed is a consultant for Optovue, and receives research support from Carl Zeiss Meditec and Topcon. There are no conflicting relationships for any other author. Purpose A) to assess the variability in vessel density (VD) measurements across three OCTA devices B) to identify a method that offers the least amount of variation in VD 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
1
20
0
2
Order By: Relevance
“…A negative association between vessel density and increasing DR severity at both the superficial and deep capillary plexuses has been repeatedly identified [60][61][62]. Though quantitative vessel metrics on OCTA have been shown to have low reproducibility between devices, certain OCTA platforms provide color coded perfusion maps based on the vessel density of normal eyes [52]. These maps can help providers track DR severity and assess vessel loss in conjunction to disease progression (Fig.…”
Section: Vascular Changesmentioning
confidence: 95%
See 1 more Smart Citation
“…A negative association between vessel density and increasing DR severity at both the superficial and deep capillary plexuses has been repeatedly identified [60][61][62]. Though quantitative vessel metrics on OCTA have been shown to have low reproducibility between devices, certain OCTA platforms provide color coded perfusion maps based on the vessel density of normal eyes [52]. These maps can help providers track DR severity and assess vessel loss in conjunction to disease progression (Fig.…”
Section: Vascular Changesmentioning
confidence: 95%
“…Though FAZ can be assessed at both the deep capillary plexus and superficial capillary plexus, there is evidence to suggest that the retinal plexuses meet at the edge of the FAZ and it is, therefore, preferable to measure the FAZ on the superficial or the full retinal depth projection [50]. Assessing FAZ area on the full retinal depth projection obviates the need for segmentation and accompanying errors, increasing the measurement's reproducibility [51,52]. Clinically, assessing FAZ enlargement over time can be a useful tool for following DR progression ( Fig.…”
Section: Faz Enlargementmentioning
confidence: 99%
“…There have been a number of excellent studies that have highlighted the potential power of OCT-A in discriminating diabetic status. [17][18][19][20][21] In particular, pioneering work by Durbin et al 7 demonstrated the ability of measuring retinal microvasculature to distinguish diabetic status in patients. In their albeit small cohort they demonstrated highest area under the ROC curve (i.e., AUC) of 0.893 for measures of the vessel density in the superficial capillary network.…”
Section: Discussionmentioning
confidence: 99%
“…For contrast, the results of our study were compared with those that instead employed an Otsu global threshold, which is based on minimizing grayscale variance within above-threshold and below-threshold classes and which has also been used in analysis of OCTA metrics, including on CC angiograms. 3 , 24 , 25 The study method was otherwise repeated exactly, and cohort characteristics remained the same. The Figure shows an example of the same angiogram after the binarization step in our study, using the Phansalkar local and Otsu methods.…”
Section: A Casementioning
confidence: 99%